An approach towards the reconstruction of regulatory networks - Pereira, Rafael Teodósio; Costa, Hugo; Mendes, Rui (Revista ComInG - Communications and Innovations Gazette, 2016)
Currently, one of the main issues addressed in the bioinformatics field is understanding the structure and behaviour of complex molecular interaction networks. Since most of the information available belongs to biomedical literature, a large part of this task entails selecting the relevant articles from a large body of papers. However, due to the rapidly increasing number of scientific papers, it is quite difficult to read all  the  papers that have been published about this subject. In order to accomplish this, this work is focused on developing methods for retrieving information from biological databases, gathering as much information as possible; to create an integrated repository, that is able to store and load this data and also to design a pipeline to allow the reconstruction of regulatory networks through using Biomedical Text Mining techniques.